2019
DOI: 10.1007/s10704-019-00377-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlating fracture toughness and fracture surface roughness via correlation length scale

Abstract: Fracture toughness of a material depends on its microstructure and the imposed loading conditions. Intuitively, the resultant fracture surfaces must contain the information about the interlacing of these intrinsic (microstructure) and extrinsic (imposed loading) characteristics. Mandelbrot's revelation that fracture surfaces are fractals, excited both the scientific and engineering communities, spurring a series of works focused at correlating the fracture toughness and the fracture surface roughness. Unfortun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…4(b)]. This is significantly lower than the values of the actual roughness exponent observed for cracked aluminum alloys [38][39][40]. There is very little difference between the exponent values in the two directions ζ x and ζ y , although initially ζ x is slightly larger.…”
Section: B Roughnessmentioning
confidence: 83%
“…4(b)]. This is significantly lower than the values of the actual roughness exponent observed for cracked aluminum alloys [38][39][40]. There is very little difference between the exponent values in the two directions ζ x and ζ y , although initially ζ x is slightly larger.…”
Section: B Roughnessmentioning
confidence: 83%
“…The aim of quantitative fractography is to find well defined mathematical descriptors which represent the complex topographic morphology of fracture surfaces. These complex morphologies encode the interlacing of the material's microstructure and intrinsic mechanical properties with the externally applied loads and environmental conditions 30 . For brittle materials, such as ceramics, the fracture process is often observed to take place using two alternating micromechanisms: transgranular and intergranular crack growth.…”
Section: Resultsmentioning
confidence: 99%
“…They found a correspondence between the Charpy impact absorption and the fractal dimension by the fractal analysis of this contour structure [2]. Another study revealed that K Ic can be estimated by extracting the roughness of a fracture surface measured by stereo imaging using an electron microscope [2,3]. From an engineering perspective, it is time-consuming and expensive to obtain the 3D information of a fracture surface; thus, it is desirable to estimate parameters of fracture process such as K Ic from two-dimensional (2D) images, which can be acquired at a relatively low cost.…”
Section: Introductionmentioning
confidence: 99%